Teacher-Student Interaction Patterns as a Process of Improving Student Discipline at the Darul Ulum Mudik Tampang Integrated Islamic Boarding School - Coil Coil; Afrinaldi Afrinaldi; Wedra Aprison; Charles Charles; Hidayani Syam (PT Publikasiku Academic Solution, 2025)
This research is motivated by the problem of student indiscipline at the Darul Ulum Mudik Tampang Integrated Islamic Boarding School, such as late class attendance, rule violations, lack of responsibility, and disrespectful behavior toward teachers and peers. The purpose of the study is to explain the teacher-student interaction patterns in improving discipline, as well as their supporting and inhibiting factors. The method used was qualitative descriptive, conducted through interviews, observations, and documentation, with fiqh teachers as key informants, as well as the head of the foundation and grade VIII students as supporting informants. Data analysis was carried out through reduction, presentation, and verification, with validity ensured through thorough observation and triangulation. The results of the study reveal four main interaction patterns: (1) Islamic example, where teachers serve as role models in discipline and worship; (2) dialogical communication through discussion, advice, and evaluation; (3) personal supervision and guidance; and (4) the application of rewards and punishments. Supporting factors include teachers’ examples, open communication, a conducive pesantren environment, and cooperation with parents. Inhibiting factors include less effective communication, inconsistent enforcement of rules, and low student motivation.